The Comedia Unbound. Issue 2 (3rd April 2022) - Fuchs, Barbara
Abstract: While the 2020 COVID-19 pandemic was disastrous for theater companies everywhere, the comedia was arguably energized by its constraints. The En compañía de los clásicos initiative in Spain, the theatrical presentations at the Association for Hispanic Classical Theater (AHCT) virtual conference in July 2020, and the reimagined virtual LA Escena Festival of Hispanic Classical Theater suggest that 2020 may have been a banner year for comedia . The engagement with the classics by cutting-edge companies producing durational, site-specific, participatory, and immersive theater revealed novel artistic possibilities and engaged new audiences, radically transforming the sense of what is possible when staging the corpus. At the same time, and even as individual companies grappled with the impact of the pandemic, the larger institutional landscape of theater in Spain continued to promote a transatlantic narrative of comedia that argues for its relevance beyond Spain itself. The comedia thus appears doubly unbound : newly freed from formal constraints, and promoted in and to a broader geography.